Emerging Prospects of Exosomes for Cancer Treatment: From Conventional Therapy to Immunotherapy. Issue 51 (5th October 2020) - Nam, Gi‐Hoon; Choi, Yoonjeong; Kim, Gi Beom; Kim, Seohyun; Kim, Seong A; Kim, In‐San
Abstract: Exosomes are a class of extracellular vesicles of around 100 nm in diameter that are secreted by most cells and contain various bioactive molecules reflecting their cellular origin and mediate intercellular communication. Studies of these exosomal features in tumor pathogenesis have led to the development of therapeutic and diagnostic approaches using exosomes for cancer therapy. Exosomes have many advantages for conveying therapeutic agents such as small interfering RNAs, microRNAs, membrane‐associated proteins, and chemotherapeutic compounds; thus, they are considered a prime candidate as a delivery tool for cancer treatment. Since exosomes also provide an optimal microenvironment for the effective function of immunomodulatory factors, exosomes harboring bioactive molecules have been bioengineered as cancer immunotherapies that can effectively activate each stage of the cancer immunity cycle to successfully elicit cancer‐specific immunity. This review discusses the advantages of exosomes for treating cancer and the challenges that must be overcome for their successful clinical development. Abstract : Exosomes are nano‐sized vesicles secreted by cells that reflect features of parental cells and play critical roles in intercellular communication. Exosomes are suitable for cancer treatment by providing an optimal environment to convey various bioactive molecules. The advantages of using exosomes for cancer treatment, from conventional therapy to immunotherapy, and challenges to be solved for clinical usage are reviewed.